Diabetogenic Metabolits of Tryptophan - Meyramov, G.G.; Kohnert, K.-D.; Shaybek, A.S.; DuPont, O.-N.; Abdraimova, A.G. (Fundamental and Experimental Biology, 2024)
The analysis of results investigations of mechanisms of diabetogenic activity of metabolits of abnormal tryptophan metabolism as Xanthurenic acid (XA) are presented in review. Among more than 30 diabetogenic chemicals widely known today XA only is formed in animals and elderly human as result of disturbances of tryptophan metabolism. The influence of XA on histostructure of pancreatic islets and on insulin content in B-cells as mechanisms of diabetogenic action and of its prevention are investigated by authors. It was showed that Xanthurenic acid induced diabetes determined by: direct damage of B-cells by Xanthurenic acid accom-panied by marked histological changes in islets as destruction and necrosis of B-cells, marked decreasing of insulin content in cytoplasm of cells; by forming of complex XA-insulin that result overstrain of B-cells; by alteration of islet’s capillaries and of blood microcirsulation.